A NEW FIELD OPENED TO IRRIGATION: SURUC PLAIN IRRIGATION PROJECT AND CURRENT STATUS QUO - Fatma ÖCAL KARA (Fırat University, 2019)
In the world, the need for food and water shows increase in parallel with the increase in world population. However, water resources are limited and current drought resulting from global climate changes leads to decrease in that important resource gradually. Unfortunately, agricultural sector have been affected mostly due to that change, because agricultural production depends on nature and climate conditions, so the most water consumption occurs in the agriculture sector. Therefore, water policy has gained importance in Turkey as worldwide and modern irrigation techniques have been started to implement. Suruc Plain Irrigation Project, which took place in the scope of Southeastern Anatolia Project, is a project that has been done with the aim of being able to use water sources efficiently. The strongest part of the project is that it includes Suruc Tunnel which is the biggest irrigation tunnel in Turkey and the fifth biggest irrigation tunnel in the world. Thanks to the water pumped from Ataturk Dam, 94.814 hectares gross area is able to be irrigated. The difference between Suruc Plain Irrigation Project and Harran Plain Irrigation Project is that the first one was planned as a suitable agricultural production with pressurized irrigation system for producers. Salinity encountered in Harran Plain has become a significant example for the design of Suruc Plain Irrigation Project. In this study, it is referred to the importance of water by taking global climate changes into consideration. Besides, it is aimed to give an outline of Suruc Plain Irrigation Project and to assert both current status quo and the possible problems that could be encountered. It is also referred to possible precautions before the plain is opened to irrigation completely. It is expected from this Project to increase in agricultural productivity and product range, to increase in the level of income in the countryside and urban region with the help of